A Time-Overlapping Multiplex VLC System for End-Edge Data Transmission. (10th August 2021) - Fu, Tingting; Zhu, Huanghong; Hai, Han; Lao, Haksrun
Abstract : Communication is one of the most important foundations in the Internet of Things. Although some cutting-edge technologies, such as 5G, have greatly empowered edge computing, electromagnetic interference and pollution make them impracticable in many environments. The visible light communication (VLC) is a new type of wireless communication technology with appealing benefits not presented in radio communications. VLC allows a lamp or other light source to not only serve as illumination but also simultaneously transmit data. Although traditional VLC multiplexing technologies have been able to achieve a high-speed data transmission rate, they require all receivers to use the same modulation means. In many scenarios, various-type receivers coexist; it is costly to incorporate multiple senders to implement adaptive content distribution in on-demand services. In this paper, we propose a new type of VLC multiplexing system, which realizes end-edge data transmission through pulse position modulation (PPM), pulse width modulation (PWM), and pulse amplitude modulation (PAM) simultaneously. Therefore, one edge server can serve multiple types of end-users without interference. In order to evaluate the performance of the system, we conduct experiments with different settings of communication distance, communication angle, and different environmental light conditions. For three modulations, the proposed system can achieve a transmission speed three times as that for a single modulation, and reach the accuracy rate of up to 99% within the proper communication range.